A 2-year longitudinal study of anxiety caused by COVID-19 and job burnout among Iranian healthcare workers - Ramin Rahmani; Venus Sargazi; Mehdi Shirzaee Jalali; Maryam Farhadian; Mohammad Babamiri (Scientific Reports)
Abstract Limited longitudinal studies can be found to describe the psychological effects of COVID-19 on healthcare workers (HCW); Therefore, the present study aimed to investigating the anxiety caused by COVID-19 (COV-anxiety) and job burnout (JB) among a sample of Iranian HCW during this pandemic longitudinally. This longitudinal study performed on 310 Iranian HCW. The data collection is done twice during 2020 and 2022. The Corona Diseases Anxiety Scale (CDAS) and the Maslach Burnout Inventory (MBI) have been used through online platform (Google Form). Using frequency tables, Paired-samples T tests, Pearson correlations as well as linear regression modeling data were analyzed through SPSS 16. While reductions observed in prevalence of COV-anxiety in time 2, the prevalence of severe levels of JB dimensions increased in time 2 compared to time (1) Negative correlations existed between JB and COV-anxiety. Moreover, using multivariate linear regressions, we found that COV-anxiety and JB were the final predictors of each other both in time 1 and (2) Despite the positive association between COV-anxiety and JB, increasing in JB levels with respect to decreasing in COV-anxiety levels highlights the existence of other risk factors that should be considered in future research.